Optimization of coating materials on jaggery for augmentation of storage quality - KUMAR, ANAND; CHAND, KHAN; SHAHI, N C; KUMAR, ANIL; VERMA, A K (The Indian Journal of Agricultural Sciences, 2017)
Storage of jaggery is highly influenced by surrounding environment due to presence of sugars and mineral salt which are hygroscopic in nature. The investigations were carried out to evaluate the effect of coating materials on jaggery cubes for improvement of shelf life during storage. A new technology is required to prolong the shelf life of this commodity. Edible coating could perform one of the good alternatives as it has the capability to barrier the water loss. Hence jaggery cubes were coated with various ratio of CMC and HPMC concentration in glycerol solution and total concentration of CMC and HPMC (0.66, 1, 1.5, 2, 2.34 g/100ml) were taken into account for the study. The parameters such as moisture content, pH, total viable count (TVC) and reducing sugar were analyzed at an interval of 45 days and all these responses were analyzed statistically using design expert software to determine the significant results. The study determined that moisture content of edible coated jaggery decreased with increase of concentration of glycerol and total concentration of CMC and HPMC while TVC decreased with increase in the ratio of CMC and HPMC. The most favorable regressors of influencing factors obtained by compromise optimization of the responses were; 75:25 ratios of CMC and HPMC, 8 ml/100ml concentration of glycerol and 1.51 gm/100ml of total concentration CMC and HPMC recommended for coating the jaggery before storage to enhance the self-life.